Advancing patient-centered cancer care: a systematic review of electronic patient-reported outcome measures - Salmani, Hosna; Nasiri, Somayeh; Alemrajabi, Mahdi; Ahmadi, Maryam (Frontiers in Rehabilitation Sciences, 2024)
BackgroundElectronic Patient-Reported Outcome Measures (ePROMs) have emerged as valuable tools in cancer care, facilitating the comprehensive assessment of patients’ physical, psychological, and social well-being. This study synthesizes literature on the utilization of ePROMs in oncology, highlighting the diverse array of measurement instruments and questionnaires employed in cancer patient assessments. By comprehensively analyzing existing research, this study provides insights into the landscape of ePROMs, informs future research directions, and aims to optimize patient-centred oncology care through the strategic integration of ePROMs into clinical practice.MethodsA systematic review was conducted by searching peer-reviewed articles published in academic journals without time limitations up to 2024. The search was performed across multiple electronic databases, including PubMed, Scopus, and Web of Science, using predefined search terms related to cancer, measurement instruments, and patient assessment. The selected articles underwent a rigorous quality assessment using the Mixed Methods Appraisal Tool (MMAT).ResultsThe review of 85 studies revealed a diverse range of measurement instruments and questionnaires utilized in cancer patient assessments. Prominent instruments such as the European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire Core 30 (EORTC QLQ-C30) and the Patient Reported Outcome-Common Terminology Criteria for Adverse Events (PRO-CTCAE) were frequently referenced across multiple studies. Additionally, other instruments identified included generic health-related quality of life measures and disease-specific assessments tailored to particular cancer types. The findings indicated the importance of utilizing a variety of measurement tools to comprehensively assess the multifaceted needs and experiences of cancer patients.ConclusionOur systematic review provides a comprehensive examination of the varied tools and ePROMs employed in cancer care, accentuating the perpetual requirement for development and validation. Prominent instruments like the EORTC QLQ-C30 and PRO-CTCAE are underscored, emphasizing the necessity for a thorough assessment to meet the multifaceted needs of patients. Looking ahead, scholarly endeavours should prioritize the enhancement of existing tools and the creation of novel measures to adeptly address the evolving demands of cancer patients across heterogeneous settings and populations.